Macrophage SREBP1 regulates skeletal muscle regeneration - Oishi, Yumiko; Koike, Hiroyuki; Kumagami, Naoki; Nakagawa, Yoshimi; Araki, Masaya; Taketomi, Yoshitaka; Miki, Yoshimi; Matsuda, Shigeru; Kim, Hyeree; Matsuzaka, Takashi; Ozawa, Hitoshi; Shimano, Hitoshi; et al. (Frontiers in Immunology, 2024)
Macrophages are essential for the proper inflammatory and reparative processes that lead to regeneration of skeletal muscle after injury. Recent studies have demonstrated close links between the function of activated macrophages and their cellular metabolism. Sterol regulatory element-binding protein (SREBP1) is a key regulator of lipid metabolism and has been shown to affect the activated states of macrophages. However, its role in tissue repair and regeneration is poorly understood. Here we show that systemic deletion of Srebf1, encoding SREBP1, or macrophage-specific deletion of Srebf1a, encoding SREBP1a, delays resolution of inflammation and impairs skeletal muscle regeneration after injury. Srebf1 deficiency impairs mitochondrial function in macrophages and suppresses the accumulation of macrophages at sites of muscle injury. Lipidomic analyses showed that reduction of major phospholipid species in Srebf1 -/- muscle myeloid cells. Moreover, diet supplementation with eicosapentaenoic acid restored the accumulation of macrophages and their mitochondrial gene expression and improved muscle regeneration. Collectively, our results demonstrate that SREBP1 in macrophages is essential for repair and regeneration of skeletal muscle after injury and suggest that SREBP1-mediated fatty acid metabolism and phospholipid remodeling are critical for proper macrophage function in tissue repair.